Pengaruh Orientasi Kewirausahaan dan Literasi Digital terhadap Kinerja UMKM Kuliner dengan Efikasi Diri sebagai Variabel Mediasi di Jakarta Selatan - Rizki Amalia; Agus Wibowo; Ari Saptono (Indo Publishing, 2026)
This study aims to examine the influence of Entrepreneurial Orientation and Digital Literacy on the Performance of Culinary MSMEs with Self-Efficacy as a Mediating Variable in South Jakarta. The population in this study consists of MSME actors registered in the Jakpreneur program by the DKI Jakarta Cooperatives, Small and Medium Enterprises Office (Dinas PPKUKM). The recommended sample size for this study is 63 MSME actors to ensure that the research results can represent the population with an adequate level of confidence. This study uses Structural Equation Modeling (SEM) data analysis techniques with the Partial Least Square (PLS) approach, analyzed using SmartPLS software version 4. The results show that Entrepreneurial Orientation has a positive and significant effect on MSME Performance. Digital Literacy has a positive and significant effect on MSME Performance. Self-Efficacy has a positive and significant effect on MSME Performance. Entrepreneurial Orientation has a positive and significant effect on Self-Efficacy. Digital Literacy has a positive and significant effect on Self-Efficacy. Entrepreneurial Orientation has a significant indirect effect on MSME Performance through Self-Efficacy. And Digital Literacy has a significant indirect effect on MSME Performance through Self-Efficacy